FEMININE ROMANTIC DISCOURSE: STRATEGIC WAYS OF THE PRAGMATIC-INTERROGATIVE COMMUNICATIVE TACTIC REALISATION - Oleksandra S. Romaniuk (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2019)
The research demonstrates the potential of the complex approach to the study of interpersonal communicative effectiveness, considering such interdependent variables as objective and subjective integrative features and the strategic ways of increasing the communicative effectiveness. The complex approach also involves the communicative-pragmatic sphere “the external context” and the cognitive sphere “the internal context”. The strategic ways are considered as a powerful tool, providing successful romantic communication. The paper focuses on the pragmatic-interrogative communicative tactic at the second stage ‘Pragmatics of Romantic Relationship’ within the Feminine Romantic Discourse, regarding the strategic ways of effective feminine communicative moves, namely discourse features of the interrogatives. Pragmatic-interrogative communicative tactic is implemented by the relevant Feminine Communicative Moves (Previous Dating Experience?, Momentous Event?, Ideal Partner?, Dating Evaluation?, Personal Plans for Future?, Self-Praise?, Ideal Relationship?, Family?), presented by the female contestants (N=99) of the dating-show “The Bachelor US”. The feminine communicative moves are aimed at revealing the pragmatics of romantic relationship. The paper also suggests that the cross-cultural awareness of effective communication is mutually beneficial for both native speakers and non-native speakers, helping easily to overcome the communication barriers and develop the greater self-confidence of the female partners. It is concluded that the non-strategic implementation of the pragmatic-interrogative communicative tactic usually causes communication failures, involving considerable risks of ruining the interpersonal romantic relationship. The findings of the interdisciplinary research apart from the practical implications have important theoretical implications. The latter makes a significant contribution to the study of interactional sociolinguistics (the language in its social context used in interaction by closely observing a certain speech event in a particular community), gender studies (the language and gender alignment), conversation analysis (the structural organisation of spoken interaction), discourse analysis (the genres of discourse and discourse units: communicative moves, tactics and strategies), interpersonal pragmatics (the pragmatic communication model of interpersonal relationship development), cross-cultural communication (the cross-cultural awareness of the interpersonal communication). The current research along with the others, presented by the author, have sought to contribute to the romantic discourse issues, revealing the strategic ways of the interpersonal effective communication and the causes of the communication failures at every stage of the romantic relationship pragmatics.